Using drawing to learn about figurative language among tertiary EFL English literature students - Clara Boon Ing Ling; Che Aleha Ladin; Jia Wei Lim (Studies in English Language and Education)
Visual art has gained popularity in education and highlighted remarkable results in terms of improving the learning experience. This has triggered a response to investigate how visual art, particularly drawing, can be applied in an educational setting. Nevertheless, there is still a missing link on how drawing functions as a tool for tertiary English as a Foreign Language (EFL) English Literature students to learn about, specifically, figurative language. This paper employs an action research method to investigate how drawing using soft pastels is used to scaffold learning about figurative language at the same time, study its benefits. Using selected literary texts involving mainly eleven tertiary EFL English Literature students, this action research qualitative study incorporates Richard Mayer’s Cognitive Theory of Multimedia Learning in three repeated cycles. This investigation may be construed as a means to transition from conventional pedagogical methodologies into contemporary paradigms, functioning as a facilitative instrument for the amalgamation of knowledge about learning literature while enhancing confidence, higher-order cognitive skills, and expressive capabilities. It allows educators to adapt their approaches, stimulating increased reflection and participation. The findings delineate two primary strategies employed in elucidating the efficacy of incorporating drawing as a pedagogical tool for English Literature students, i.e., mining to trigger thoughts and engaging with senses to assist EFL students in learning about figurative language. It can be asserted that integrating drawing empowers individuals to formulate idiosyncratic responses by exploring concepts, articulating emotions, validating responses, and discerning the profound dimensions of literary texts.